A Study on Aids Awareness Among College Students: Promoting HIV/AIDS awareness and education among college students (Journal of Advances and Scholarly Researches in Allied Education, 2012)
AIDS is the most dreadful enemy of humanrace; which is taking epidemic dimensions gradually all over the world. It hasentered the Indian soil with disastrous implications on millions of peopleliving in rural, urban and tribal communities. Every state in India isexperiencing an increase rate of the transmission of HIV. Since youth are theeasily approachable targets of HIV/AIDS, they are also considered as thevulnerable group. Everyone has a right to information and education aboutHIV/AIDS and these facts of life will help our young people to protectthemselves from the infection of AIDS. An overwhelming section of ourpopulation is not aware about this dreaded disease, specially the illiterateand socially deprived people. Peer education proves to be the most effective wayof changing attitudes and practices related to risk taking behaviour amongeducated youth. Therefore it is easier for such youth to reach other andfurther; spread the knowledge related to HIV/AIDS.